Geochemical features and genesis of shale gas in the Jiaoshiba Block of Fuling Shale Gas Field, Chongqing, China - Wei, Xiangfeng; Guo, Tonglou; Liu, Ruobing (Journal of Natural Gas Geoscience, 2016)
Taking natural gas from marine strata of the Wufeng–Longmaxi Formation in the Jiaoshiba Block of the Fuling Shale Gas Field as a research subject, the analyses of the gradients of shale gas and carbon isotope shows that the natural gas from the Jiaoshiba area belongs to a high-quality hydrocarbon gas. The contents of methane range 97.22%–98.41%, with a little amount of ethane and propane, an average wetness of 0.74%, and little amount of non-hydrocarbons such as CO2, N2, H2, however, there's no H2S. The carbon isotopes of methane, ethane, and propane are characterized by their complete isotopic reversal (δ13C1 > δ13C2 > δ13C3). The natural gas from the Wufeng–Longmaxi Formation comes from the source rocks of the same formation, it classifies as a typical shale gas. According to the statistical determination criterion, natural gas in the Jiaoshiba area is derived from the sapropelic source rocks, which is a result of high-temperature pyrolysis. It is the product of mixing primary kerogen pyrolysis and secondary pyrolysis of crude oil, with apparent features of secondary pyrolysis of oil. The reason for the complete carbon isotopic reversal is the mixing of the two aforementioned gasses. Moreover, it has some sort of relationship with the loss function of shale gas after the Late Yanshan.